Tunisia's troubles. Issue 3 (16th March 2019) - Unknown
Abstract : Often considered the sole potential success of the Arab Spring, Tunisia is now in a perilous position. If Tunisia's troubles persist, the best likely scenario it faces is stagnation, accompanied by a gradual return towards more authoritarian government. Yet recent unrest across North Africa and the broader region suggests that more turbulent outcomes are also possible.